Diseases in dogs: necropsy observation - Chooi, Kum Fai; Thuthan, Pandiyaraja; Sheikh Omar, Abdul Rahman (Universiti Pertanian Malaysia, 1989)
Morbidity in dogs was associated mainly with diseases or abnormal it if in the Pansystemic, digestive and respiratory systems in that order. In the pansystemic category, poisoning and carnine distemper' were most common. Ancylostomiasis and bronchopneumonia were the main Fndings in the digestive and respiratory systems 'respectively.